Effect of culture raising techniques on mycelial growth characteristics and the fruit body yield potential in strains of Volvariella volvacea - Ahlawat, Om Parkash (Mushroom Research, 2017)
The cultures raised through tissue culture and multispore culture techniques in three strains of V. volvacea showed variations in mycelial growth characteristics compared with the original cultures both on Malt Extract Agar and the pounded paddy straw. The mycelial growth characteristics of multispore cultures were of ‘atypical’ type while those obtained from original and tissue cultures were of ‘typical’ type. The activities of exoglucanase, endoglucanase, xylanase and β–glucosidase were higher in original cultures or tissue cultures as compared to multispore cultures in all the three strains. The fruit body yield response of tissue cultures varied in different strains. In strain DMRO-463, the tissue culture gave slightly higher fruit body yield (31.85 and 31.84 kg/q dry substrate) compared to original culture (29.39 and 23.01 kg/q dry substrate) in two cultivation trials, while in strain DMRO-484, the original culture gave slightly higher fruit body yield (31.92 and 24.16 kg/q dry substrate) than the tissue culture (31.51 and 23.64 kg/q dry substrate). The third strain DMRO-185 gave inconclusive results, where in 1st trial; the original culture gave significantly higher fruit body yield compared to tissue culture, while in 2nd trial the fruit body yield was at par in both types of cultures. In all cases the multispore cultures gave lower fruit body yield compared to the original and tissue cultures.